THE EFFICIENCY OF GRAVID AEDES TRAP IN COLLECTING AEDES MOSQUITOES IN AN NHON TOWN, BINH DINH PROVINCE - Nguyen Xuan, Quang; Do Cong, Tan; Vo Thi, Phuong Nhi (TẠP CHÍ PHÒNG CHỐNG BỆNH SỐT RÉT VÀ CÁC BỆNH KÝ SINH TRÙNG, 2024)
The use of Gravid Aedes Trap (GAT) for collection of Aedes mosquitoes in Nhon Hoa ward, An Nhon town, Binh Dinh province was conducted from February to June 2022. The result showed that: In Nhon Hoa, 20 GAT traps were used in 100 days and collected 1486 Aedes mosquitoes; in the outside, the density of Ae. Aegypti and Ae. albopictus was 4.32 ± 2.11 mosquitoes/trap/20 days and 8.94 ± 2.77 mosquitoes/trap/20 days; respectively; in the inside, the density of Ae. Aegypti and Ae. albopictus was 14.64 ± 5.19 mosquitoes/trap/20 days and 1.82 ± 1,167 mosquitoes/trap/20 days. The use of GAT traps helps to decrease the risk of dengue fever outbreak at the locality. The population of Ae.aegypti and Ae. albopictus accounted for 63.8% and 36.2%, respectively. In the outside, the population of Ae.aegypti and Ae. albopictus accounted for 32.58% and 67.42%, respectively. In the inside, the population of Ae.aegypti and Ae. albopictus accounted for 88.94% and 11.06%, respectively. In the outside, 98% of the traps collected Ae. aegypti and 100% of the traps collected Ae. albopictus; since setting the traps to the 5th day, there were Aedes mosquitoes in the traps. In the inside, 100% of the traps collected Ae. aegypti and 66% of the traps collected Ae. albopictus; since setting the traps to the 3th day, there were Aedes mosquitoes in the traps. In the outside, 4% of the traps collected Ae. aegypti larvae and 2% of the traps collected Ae. albopictus larvae. In the inside, 10% of the traps collected Ae. aegypti larvae and there was no Ae. albopictus larvae; since setting the traps to the 7th day, there were Ae. aegypti larvae in the traps. Key words: Gravid Aedes Trap, Dengue vector, Nhon Hoa ward.